Swept Away - Travolti da un insolito destino nell'azzurro mare d'agosto - Lina Wertmüller (1974)
A rich woman, Raffaella, and some friends rent a yacht to sail the Mediterranean Sea during summer. The sailor, Gennarino, who is a communist, does not like this woman but has to bear with her bad mood. One day she wakes up late in the afternoon and asks to be taken to land where everyone had gone earlier. Gennarino sets up a boat but during the trip, the boat breaks down. They spend the night in the middle of the sea.
Keywords: Adventure, Comedy, Drama